Stability of Bar Code Information Stored in Magnetic Nanowire Arrays - Eduardo Cisternas; Eugenio E. Vogel; Julián Faúndez (Advances in Condensed Matter Physics)
Firmware applications such as security codes, magnetic keys, and similar products can be stored in magnetic bar codes similar to optical bar codes. This can be achieved on the triangular lattice present in porous alumina, whose pori can be filled by magnetic material, over which magnetic bar codes can be inscribed. We study the conditions to improve the durability of the stored information by minimizing the repulsive energy among wires with parallel magnetization within the same bar but interacting with attractive energy with wires in the neighboring bar. The following parameters are varied to minimize the energy of the system: relative amount of magnetization orientation within the bar code area in any orientation, width of the bars, and distribution of wider bars to the outside or to the inside of the code. It is found that durability of the code is favored for equal amount of magnetization in each direction, abundance of narrow bars trying to locate a few wider ones towards the center. Three real commercial optical bar codes taken at random were mapped into magnetic bar codes; it is found that the corresponding magnetic energies are similar to those analyzed here which provides a realistic test for this approach.